The customer for R&D is always wrong! - Frosch, Robert A.
Robert A. Frosch, in his IRI Medalist Address, deplores management fads that sever the links between knowledge resources and thereby prevent effective R&D management.
Effective R&D management depends upon interconnected knowledge and the interconnection of people who possess that knowledge. Current fads in corporate restructuring ignore that.
The current fad of corporate managements, taking short-term views and distributing R&D assets to operating divisions, is like a farm investor who is interested only in harvesting and will not invest in planting, cultivating or irrigating; neither is likely to get much good harvest for very long. Applications R&D depends on using the interconnectedness of many kinds of knowledge, and thus depends on the close interaction of research people with that knowledge. The destruction of these key connections, together with the fact that the customer for R&D is always wrong about the requirements, will ensure future trouble.
Keywords: R&D.